Supporting Sustainable Development Goals through Community Service at Posbindu PTM for Non-Communicable Diseases in Kecamatan Bogor Timur - Suatmi, Bernadetta Dwi; Suhartono, Sugi; Mulyani, Mulyani; Dema, Yosef (PT FORMOSA CENDEKIA GLOBAL, 2024)
Non-communicable diseases (NCDs), including heart disease, stroke, cancer, diabetes, and chronic lung disease, are collectively responsible for the majority of deaths worldwide. To reduce the mortality rate caused by NCDs, the United Nations set goal 3 of the Sustainable Development Goals (SDGs): to ensure healthy lives and promote well-being for all at all ages. To support this goal, community services of IBI Kwik Kian Gie have participated in the Posbindu PTM program in RW 06, Kelurahan Katulampa, Kecamatan Bogor Timur. This activity was held in June, July, and August 2023. Based on the evaluation of the Posbindu PTM program, it can be concluded that Posbindu PTM in RW 06, Kelurahan Katulampa, Kecamatan Bogor Timur, should be continued with some evaluations and improvements for future programs.